Estimating selection models without instrument with Stata - D’Haultfœuille, Xavier (Institutional Knowledge at Singapore Management University, 2020)
This article presents the eqregsel command for implementing the estimationand bootstrap inference of sample selection models via extremal quantile regression. The command estimates a semiparametric sample selection model withoutinstrument or large support regressor, and outputs the point estimates of the ho-mogenous linear coefficients, their bootstrap standard errors, as well as the p-valuefor a specification test.